The Application of Analytic Hierarchy Process and Topsis Methods in Selecting Outstanding Students Based on Android (Case Study: SMAN 1 Siantar Narumonda) - Yuliansyah Siregar, Andree Rizky; Pratama, Wiko; Wahyudi, Muhammad (Cattleya Darmaya Fortuna, 2023)
SMAN 1 Siantar Narumonda is a high school located on Jalan SMA Negeri Narumonda, Narumonda I, Kec. Siantar Narumonda, Toba Regency. Currently, the principal and teachers of SMAN 1 Siantar Narumonda still use manual methods in determining outstanding students using spread sheets in the Microsoft Excel program which seems very ineffective and inefficient because spread sheets can no longer meet the requirements for timeliness, speed and accuracy in data management. the number is large, so it takes quite a long time to process it because you have to look at a lot of tables in Excel. In solving the problem above, it is necessary to solve the problem by creating a decision support system using the AHP and TOPSIS methods. This research combines AHP and TOPSIS with the aim of obtaining accurate results in providing recommendations for decision makers in accordance with the objectives and implementation model carried out. Based on the results of the tests carried out, it was found that AHP and TOPSIS provide objective and reliable results in determining outstanding students. This application can speed up the selection process and reduce the potential for human error.